Are Cities Prepared for Autonomous Vehicles?: Planning for Technological Change by U.S. Local Governments. Issue 2 (3rd April 2019) - Freemark, Yonah; Hudson, Anne; Zhao, Jinhua
Abstract: Problem, research strategy, and findings: Local government policies could affect how autonomous vehicle (AV) technology is deployed. In this study we examine how municipalities are planning for AVs, identify local characteristics that are associated with preparation, and describe what effects bureaucrats expect from the vehicles. We review existing plans of the 25 largest U.S. cities and survey transportation and planning officials from 120 cities, representative of all municipalities with populations larger than 100, 000. First, we find that few local governments have begun planning for AVs. Second, cities with larger populations and higher population growth are more likely to be prepared. Third, although local officials are optimistic about the technology and its potential to increase safety while reducing congestion, costs, and pollution, more than a third of respondents worried about AVs increasing vehicle miles traveled and sprawl while reducing transit ridership and local revenues. Those concerns are associated with greater willingness to implement AV regulations, but there is variation among responses depending on political ideology, per capita government expenditures, and population density. Takeaway for practice: Municipal governments' future approaches to AV preparation will likely depend on the characteristics of city residents and local resources. Planners can maximize policy advancement if they work with officials in other cities to develop best practices and articulate strategies that overlap with existing priorities, such as reducing pollution and single-occupancy commuting.